Effect of a Six-Month Certificate Course in Health Professions Education on the Adversity Quotient of Medical Teachers: Six-Month Certificate Course in Health Professions Education and Medical Teachers - Shabbir, Bilquis (Pakistan Journal of Health Sciences, 2026)
Medical teachers frequently face high-stakes, stressful situations that challenge their emotional and professional effectiveness. Adversity Quotient (AQ) reflects an individual’s ability to withstand stress, and faculty development programs like CHPE may enhance both teaching competence and psychological resilience. Objective: To evaluate the effects of a six-month course in CHPE on the AQ of the medical teachers. Methods: The study was a pre-test post-test quasi-experimental quantitative study on 55 medical teachers who participated in the CHPE program at Fatima Jinnah Medical University, Lahore. The data were gathered on the Adversity Response Profile (ARP) questionnaire. The measurement of AQ scores was undertaken before the course and after the course. IBM SPSS Statistics version 28.0 was used to analyze the data. Results: The AQ of the participants improved significantly after the CHPE intervention (Median [IQR]: 106 [96 -118] vs. 142 [134-156]; Z = -5.943, p<0.001). Before the course, 69.1% had Low AQ and 30.9% had Moderately Low AQ. Once it was completed, 49.1% got Moderate AQ, 16.4% got Moderately High AQ, and 5.5% got High AQ. The subgroup analyses showed an increase in median AQ scores where gender and years of experience did not significantly affect the results (p>0.05). Conclusions: The six-month CHPE program had a statistically significant impact on the Adversity Quotient of the medical teachers and implied that a well-designed faculty development intervention could make academic healthcare professionals resilient and adaptive.